ABHD1 Facilitates Intermediate Filament–Mediated Endothelial Cell Chemotaxis by Regulating KRT1 and KRT2 in Diabetic Retinopathy - Xinyi Liu; Junwei Fang; Tian Niu; Xindan Xing; Xin Shi; Yu Xiao; Yuan Qu; Yan Jiang; Kangjia Lv; Tianyu Dou; Qian Zhu; Hancong Wan; et al. (Journal of Diabetes Research)
Diabetic retinopathy (DR) is one of the most common complications of diabetes and induces severe visual impairment worldwide. Endothelial cell dysfunction plays an important role in the pathogenesis of DR. Here, we keep a watchful eye on α/β-hydrolase domain–containing 1 (ABHD1), a potential regulator in lipid metabolism and neovascularization. Results revealed that ABHD1 expression increased both in retina tissues of DR patients and in high-glucose–treated human retina endothelial cells. Inhibition of ABHD1 remitted endothelial cell proliferation and migration. And GSEA uncovered that ABHD1 knockdown remits endothelial cell chemotaxis and intermediate filament (IF) might be mediated in the progress by regulating keratin 1 (KRT1) and keratin 2 (KRT2). Therefore, we assume that ABHD1 is concerned with endothelial cell proliferation and migration in DR, consequently leading to pathological neovascularization. The findings may provide a potential therapeutic target for DR.